TYPES OF HEREDITARY DISEASES FOUND IN THE POPULATION OF UZBEKISTAN AND THE REASONS FOR THE OCCASION - Sharipova Farida Salimjanovna; Azizov Elbek Abdinazar ugli; Azizova Nigora Abdinazar kizi; Omonova Zebo Rustam kizi (Scholar Express Journals, 2024)
The following are covered by the types of basic hidden diseases, which are found in the population of Uzbekistan and the reasons for their appearance. During the study, commonen genetic diseases - for example, there were cases such as Tarantikia, hemofilia, and back-cerebral muscles, analyzed. The factors that lead to their widespread, including marriages, ecological state, were considered as a lack of medical genetic advice. It is clear that preventive measures and the genetic research in the formation of a healthy generation. This topic is important in the early detection of genetic diseases in the field of health and making work on the prevention of their prevention.
Keywords: Hereditary diseases; genetics; talented